The Health Benefits of the Bioactive Compounds in Foods - Jaime, Laura; Santoyo, Susana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The development of new foods or nutraceuticals with health benefits is among today's most important issues, which presents an opportune moment for the food and/or pharmaceutical industries. However, the launch of new products should be supported by strong scientific evidence on the health benefits attributable to the intake of these bioactive food ingredients. Studies focusing on changes during the storage conditions, digestion process, intestinal absorption rates, biological mechanisms of action, or bioactivity of their metabolites are also required to establish the real contribution of these compounds to the health status of today's societies